Parity and metabolic syndrome in middle-aged Iranian women: a cross-sectional study - Munn Sann Lye; Niloufar Ahmadi; Geok Lin Khor; Syed Tajuddin B Syed Hassan; Parichehr Hanachi; Mouloud Agajani Delavar (Babol University of Medical Sciences, 2015)
Introduction: The hormonal changes that happen during pregnancy may have effects on weight, blood pressure, dyslipidaemia, and possibly metabolic syndrome. The aim of this study was to determine the association between parity and metabolic syndrome in middle-aged women in Babol, Iran.   Methods: A total number of 800 women, with the age range of 30 to 50, were selected through a systematic random sampling method and sampling propionate to size from Babol. The metabolic syndrome was diagnosed based on the criteria set by the National Cholesterol Education Program (NCEP) III. The individuals' socio-demographic characteristics, the number of live births, pregnancies, lifestyles, current physical activity, and dietary factors were assessed. Logistic regression was used to determine the independent association between parity and the prevalence of metabolic syndrome. Results: The data were obtained from 633 participants (79.1%). The women, who reported a history of gravidity or parity, had a mean score of 2.4 ± 1.0. One hundred and ten (110, 17.4%) women had less than two parities and 523(82.6%) had two or more parties. Women who developed metabolic syndrome were more likely to have a higher parity at the time of interview (p= 0.001). Women with ≥ 2 parity had significantly higher odds of metabolic syndrome (OR= 1.91, 95% CI= 1.08-3.37). In addition, logistic regression analyses were then performed to assess the association of parity with each component of the metabolic syndrome. The women with ≥ 2 parity were significantly more likely to have abdominal obesity (p= 0.010). Conclusion: Higher parity or gravidity was associated with higher prevalence of metabolic syndrome in middle-aged women. Health policy makers should work with health providers to reduce the risk of metabolic syndrome in middle-aged multipar women.